Does FIGO 2023 meet clinical needs? An analysis of challenges and limitations - Szatkowski, Wiktor; Kmieć, Aleksandra; Kluz, Tomasz; Cieślak-Steć, Małgorzata; Nowak-Jastrząb, Małgorzata Urszula; Śliwińska, Magdalena; Winkler, Izabela; Tomaszewski, Jacek; Misiek, Marcin; Blecharz, Paweł (Menopause Review/Przegląd Menopauzalny, 2025)
The International Federation of Gynecology and Obstetrics (FIGO) 2023 classification for endometrial cancer (EC) introduces significant changes by integrating molecular subtypes (POLEmut, mismatch repair deficient, p53abn, no specific molecular profile) with traditional anatomical and pathological criteria. Key updates include an expanded number of substages, the incorporation of lymphovascular space invasion (LVSI) as a prognostic factor, and a novel division of tumors into aggressive and non-aggressive categories, reflecting advancements in oncology. These updates enhance prognostic precision and inform therapeutic strategies. Non-aggressive tumors, such as low-grade endometrioid carcinomas (G1 and G2), are associated with favorable outcomes and limited invasiveness. For these cases, factors like LVSI and depth of myometrial invasion support individualized approaches, including the potential for therapy de-escalation. Aggressive tumors, including high-grade endometrioid carcinomas (G3), serous and clear cell carcinomas, and p53abn subtypes, exhibit a higher risk of recurrence and metastasis, requiring intensified treatments. However, variability in molecular and histopathological assessments poses challenges to risk stratification within this group. Despite its potential to personalize treatment, the FIGO 2023 system presents implementation challenges. Variability in assessing LVSI, sentinel lymph node ultrastaging, and molecular markers highlights the need for standardized diagnostic criteria. Additionally, tumor heterogeneity complicates classification and therapeutic decisions, necessitating more advanced diagnostic approaches. The future success of the FIGO 2023 classification depends on harmonizing diagnostic standards, improving access to molecular technologies, and validating prognostic implications through prospective studies. While this update represents a significant step forward in tailoring EC management, further refinements are required to address diagnostic and implementation challenges and improve patient outcomes.